2011
DOI: 10.2214/ajr.10.6062
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Detection on Dynamic Contrast-Enhanced MRI: Computer-Aided Diagnosis Versus Single Perfusion Parameter Maps

Abstract: CAD can improve the diagnostic performance of DCE-MRI in prostate cancer detection, which may vary according to zonal anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 34 publications
2
58
0
Order By: Relevance
“…This is expected since both use the Metropolis-Hastings Markov chain Monte Carlo (MCMC) method and similar prior information. Their only difference is that we parameterized the posterior probability distribution function p(k,σ|CTIC) with ve to optimize EES volume directly instead of calculating it via kep (ve=Ktrans/kep) [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is expected since both use the Metropolis-Hastings Markov chain Monte Carlo (MCMC) method and similar prior information. Their only difference is that we parameterized the posterior probability distribution function p(k,σ|CTIC) with ve to optimize EES volume directly instead of calculating it via kep (ve=Ktrans/kep) [7].…”
Section: Discussionmentioning
confidence: 99%
“…Tracer kinetic models such as the extended Toft model [5] that describe the enhancement process are often used to derive quantitative parameters and are increasingly used in diagnostic models [6] including computer aided diagnostic (CAD) software [7,8]. Accurate quantification that will be reproducible between different clinical sites is necessary for the widespread of DCE based CAD software.…”
Section: Introductionmentioning
confidence: 99%
“…In the entire prostate mass , accuracy was greater for CAD than for all perfusion parameters or T2WI (68 -76%); sensitivity was higher for CAD than for T2WI, initial slope, wash-in rate, slope , and washout rate (39-78%); and specificity was greater for CAD than for T2WI, k(ep), k(el), and time to peak (57-69%) (p < 0.01). Reseach concluded CAD can improve the diagnostic performance of DCE-MRI in prostate carcinoma detection, which may vary according to zone anatomy (18) . In a research by Sayed Zidan et al in 2015 , they found sensitivity of DCE-MRI, ADC at 1.2 and ADC at 1.4 in detection of prostatic carcinoma was 99 %, 84.7% and 99% respectively (P = 0.0001).…”
Section: Quantitative Approachmentioning
confidence: 99%
“…Recent studies showed an increasing interest in developing automatic diagnosis systems to detect and characterize prostate cancer on the basis of a multi-parametric MR imaging approach (Vos et al 2012, Niaf et al 2012, Sung et al 2011. The aim was to assist radiologists in making correct diagnosis decisions by providing an objective and reproducible malignancy score for suspicious targets (Niaf et al 2012, Shah et al 2012.…”
Section: Introductionmentioning
confidence: 99%